Evaluasi Efektifitas Teknologi Pencegahan Pencemaran Minyak di Kapal - Sa'adah, Nor (Politeknik Bumi Akpelni, 2023)
Rapid technological advances make the maritime industry face significant challenges in managing environmental impacts, especially oil pollution by ship. Oil pollution not only causes environmental problems but also has the potential to damage marine ecosystems, human health, and coastal economies. This problem is exacerbated by the limitations of existing technology in preventing and dealing with oil pollution from ships. This article intends to evaluate the performance of oil pollution prevention and control technology by determining the effectiveness of existing technology, called OWS, and analyzing the obstacles faced in operating OWS. The method used in this article is a qualitative description referring to several literature reviews. The literature study results show that the technology used to prevent oil pollution from ships is OWS (Oil Water Separator). OWS effectively prevents oil pollution because ships can reduce the oil content in ships' waste. Meanwhile, the obstacle faced in operating OWS is the need for more maintenance, which causes OWS performance to be not optimal.